An axillary arch - (:unkn) unknown (My University, 1996)
An axillary (axillopectoral) muscle (arch) was observed extending between the upper border of the latissimus dorsi and the lower border of the pectoralis major muscles in a 48-year-old male cadaver during our dissections. In the same cadaver, the pectoralis major muscle has entirely inserted into the most distal part of the tendon of deltoideus.
Keywords: Humans; Middle Aged; Male; Axilla; Muscle, Skeletal; Pectoralis Muscles; Reference Values